IMPLEMENTASI IOT NODE MCU DALAM PENGENDALI BEBAN LISTRIK RUMAH TINGGAL - Mesdi, Mesdi; Aryza, Solly; Wibowo, Pristisal; Anisah, Siti; Hamdani, Hamdani (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
This research discusses the electrical load controllers of the house that implements the latest system with the IOT method which replaces the general controls that activate / deactivate it near the electric load, so that a controller system design that can be controlled anywhere is made. By utilizing NodeMCU E3SP 8266 technology and Android as the control center and the internet / WIFI network as the connection media. The test results of this tool can be controlled / controlled anywhere while still connected to the internet / WIFI network.